2-Year-Olds Learning From 2D Media With and Without Parental Support: Comparing Two Forms of Joint Media Engagement With Passive Viewing and Learning From 3D - Heimann, Mikael; Hedendahl, Louise; Ottmer, Elida; Kolling, Thorsten; Koch, Felix-Sebastian; Birberg Thornberg, Ulrika; Sundqvist, Annette (Frontiers in Psychology, 2021)
The study investigates to what degree two different joint media engagement (JME) strategies affect children’s learning from 2D-media. More specifically, we expected an instructed JME strategy to be more effective than a spontaneous, non-instructed, JME strategy. Thirty-five two-year old children saw a short video on a tablet demonstrating memory tasks together with a parent. The parents were randomized into two groups: One (N = 17) were instructed to help their child by describing the actions they saw on the video while the other group (N =18) received no specific instruction besides “do as you usually do.”The parents in the instructed group used significantly more words and verbs when supporting their child but both groups of children did equally well on the memory test. In a second step we compared the performance of the two JME groups with an opportunistic comparison group (N = 95) tested with half of the memory tasks live and half of the tasks on 2D without any JME support. Results showed that the JME intervention groups received significantly higher recall scores than the no JME 2D comparison group. In contrast, the 3D comparison group outperformed both JME groups. In sum, our findings suggest that JME as implemented here is more effective in promoting learning than a no JME 2D demonstration but less so than the standard 3D presentation of the tasks.